2017
DOI: 10.3390/ma10010069
|View full text |Cite
|
Sign up to set email alerts
|

Novel AlN/Pt/ZnO Electrode for High Temperature SAW Sensors

Abstract: In order to develop a film electrode for the surface acoustic wave (SAW) devices working in high temperature, harsh environments, novel AlN/Pt/ZnO multilayers were prepared using pulsed laser deposition (PLD) systems on langasite (LGS) substrates. The AlN film was used as a protective layer and the ZnO buffer layer was introduced to improve the crystal quality of Pt films. The results show that the resistances of Pt and AlN/Pt film electrodes violently increase above 600 °C and 800 °C, respectively, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In the last years, Aluminum Nitride (AlN) became a hot topic material for many sensing applications. This is due to its good piezoelectric properties, large bandgap (6.2 eV), high temperature stability (up to 1000 °C), chemical inertness, compatibility with the process technology, that makes AlN a very interesting material for realization of various types of sensors [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. For instance, piezoelectric AlN thin films were successfully integrated in pressure sensors capable to operate in high temperature or in harsh environments conditions (e.g., combustion pressure sensors for cars) [ 8 ] or for measuring pressure fluctuations in rotating machinery such as compressors and turbines [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, Aluminum Nitride (AlN) became a hot topic material for many sensing applications. This is due to its good piezoelectric properties, large bandgap (6.2 eV), high temperature stability (up to 1000 °C), chemical inertness, compatibility with the process technology, that makes AlN a very interesting material for realization of various types of sensors [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. For instance, piezoelectric AlN thin films were successfully integrated in pressure sensors capable to operate in high temperature or in harsh environments conditions (e.g., combustion pressure sensors for cars) [ 8 ] or for measuring pressure fluctuations in rotating machinery such as compressors and turbines [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…From Figure 4a, we can see that only the Pt (111) peaks appear in these two samples. No ZnO peaks can be observed in these patterns because this this ZnO film was too thin to be detected [12]. The intensity of the Pt (111) peak is much lower for Al 2 O 3 /Pt/ZnO/LGS than Al 2 O 3 /Pt/ZnO/Al 2 O 3 /LGS.…”
Section: Resultsmentioning
confidence: 99%
“…The large FWHM of the Pt peak of Al 2 O 3 /Pt/ZnO/LGS is due to the low temperature of deposition of the ZnO buffer layer, which results in the poor crystalline qualities of both ZnO and Pt. The crystalline qualities these films are typically improved by increasing the deposition temperature to 600 °C [12]. However, we have found that by inserting an Al 2 O 3 barrier layer we can improve the crystalline quality of the ZnO buffer layer deposited at low temperatures; this was possible because of their similar crystal structures [16,17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, m is the Al mole fraction in the composite alloy and mn. For example, AlN based semiconductor materials play a significant potential applications in opto-electrics operating at deep ultraviolet since these materials' high thermal conductivity properties [3][4][5][6] and [7]. However, so far its knowledge is very limited in the field of the quantitative description of thermal conductivities with respect to Al mole fraction m and temperature T in composite semiconductor of Al m N n .…”
Section: Introductionmentioning
confidence: 99%